Perancangan Sistem IoT Perawatan Tanaman Sawi Indoor Menggunakan Protheus dan Kontrol Logika Fuzzy - Syujak, Ahmad Rois; Fitria, Fitria; Amirah, Amirah (STMIK BINA PATRIA, 2026)
The advancement of agricultural technology has encouraged the implementation of Internet of Things (IoT)-based automation systems to improve efficiency and productivity in crop cultivation, particularly in greenhouse environments. This study aims to design and implement an IoT-based automation system for indoor mustard plant cultivation using the Mamdani fuzzy logic approach. The system was developed using the ADDIE model, which consists of analysis, design, development, implementation, and evaluation stages. The system utilizes environmental parameters, including temperature, soil moisture, and light intensity, collected through sensors and processed using fuzzy logic to control actuators such as water pumps and lighting automatically. The experimental results show that the system operates in real-time with an average response time of 2.7 seconds and achieves a sensor accuracy with an average error of 2.78%. Furthermore, the system improves water usage efficiency by up to 30% compared to conventional manual methods. These results indicate that the proposed system provides an effective and adaptive solution for greenhouse management and has strong potential to support the development of smart agriculture systems. Keywords: Internet of Things, greenhouse, fuzzy logic, automation, mustard plant